Activating transcription factor-4 promotes mineralization in vascular smooth muscle cells - Masuda, Masashi (JCI Insight, 2016)
Emerging evidence indicates that upregulation of the ER stress–induced pro-osteogenic transcription factor ATF4 plays an important role in vascular calcification, a common complication in patients with aging, diabetes, and chronic kidney disease (CKD). In this study, we demonstrated the pathophysiological role of ATF4 in vascular calcification using global Atf4 KO, smooth muscle cell–specific (SMC-specific) Atf4 KO, and transgenic (TG) mouse models. Reduced expression of ATF4 in global ATF4-haplodeficient and SMC-specific Atf4 KO mice reduced medial and atherosclerotic calcification under normal kidney and CKD conditions. In contrast, increased expression of ATF4 in SMC-specific Atf4 TG mice caused severe medial and atherosclerotic calcification. We further demonstrated that ATF4 transcriptionally upregulates the expression of type III sodium-dependent phosphate cotransporters (PiT1 and PiT2) by interacting with C/EBPβ. These results demonstrate that the ER stress effector ATF4 plays a critical role in the pathogenesis of vascular calcification through increased phosphate uptake in vascular SMCs.